Gestión docente en la evaluación de aprendizajes - Muso Avilés, Cristian Raúl (2020)
The report carried out focuses on the problem that currently learning assessment is conceived as a punitive and sanctioning process little objective at the time of demonstrating the achievement of learning. The objective is to determine the execution of teaching management and the application of evaluation techniques and instruments with a view to generating a real evaluation and equitable. In response to traditional practices, the implementation estimation techniques and instruments in the teaching-learning process. In the methodology, the selection of the topic, approach of the problem, initial immersion in the field (contextualization), conception of the study design, definition of the initial study sample and access to it, data collection, data analysis, interpretation of results, elaboration of the proposal, therefore this research is of a inductive. Surveys were applied, both for teachers and students; of the analysis and interpretation of results it can be deduced that there is no necessary guidance for teachers to easily use the various evaluation techniques and instruments. It was also evidenced that there is no academic reinforcement after obtaining the results of an evaluation, position that, there are no instruments to support the achievements, progress, strengths or difficulties that a student may have in the teaching-learning process. All these criteria have served to propose guides and examples of techniques and innovative assessment instruments for application in the areas of GBS, with the purpose of projecting to teachers an orientation so that the comprehensive evaluation process and the level of achievement of the learning in a qualitative and quantitative way and help the development of students.